Slow, continuous enzyme replacement via spinal CSF in dogs with the paediatric‐onset neurodegenerative disease, MPS IIIA. Issue 3 (10th November 2016) - King, Barbara; Marshall, Neil R.; Hassiotis, Sofia; Trim, Paul J.; Tucker, Justin; Hattersley, Kathryn; Snel, Marten F.; Jolly, Robert D.; Hopwood, John J.; Hemsley, Kim M.
Abstract: Intra‐cerebrospinal fluid (CSF) injection of recombinant human lysosomal enzyme is a potential treatment strategy for several neurodegenerative lysosomal storage disorders including Sanfilippo syndrome (Mucopolysaccharidosis type IIIA; MPS IIIA). Here we have utilised the MPS IIIA Huntaway dog model to compare the effectiveness of the repeated intermittent bolus injection strategy being used in the trials with an alternate approach; slow, continual infusion of replacement enzyme (recombinant human sulphamidase; rhSGSH) into the spinal CSF using a SynchroMed II® pump attached to a spinal infusion cannula. The ability of each enzyme delivery strategy to ameliorate lesions in MPS IIIA brain was determined in animals treated from ∼three‐ to six‐months of age. Controls received buffer or no treatment. Significant reductions in heparan sulphate (primary substrate) were observed in brain samples from dogs treated via either cisternal or lumbar spinal CSF bolus injection methods and also in slow intra‐spinal CSF infusion‐treated dogs. The extent of the reduction differed regionally. Pump‐delivered rhSGSH was less effective in reducing secondary substrate (GM3 ganglioside) in deeper aspects of cerebral cortex, and although near‐amelioration of microglial activation was seen in superficial (but not deep) layers of cerebral cortex in both bolus enzyme‐treated groups, pump‐infusion of rhSGSH had little impact on microgliosis. While continual low‐dose infusion of rhSGSH into MPS IIIA dog CSF reduces disease‐based lesions in brain, it was not as efficacious as repeated cisternal or spinal CSF bolus infusion of rhSGSH over the time‐frame of these experiments.